2018
DOI: 10.1021/acscatal.8b00460
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Electrocatalytic Performance of Palladium with the Electronic Metal–Support Interaction: A Case Study on Oxygen Evolution Reaction

Abstract: The present work reports a general approach to improve the electrocatalytic property of noble metal through regulating its electron status by introducing the electronic metal–support interaction (EMSI). As a case study, the catalytic activity of metallic Pd toward oxygen evolution reaction (OER) in alkaline solution has been significantly promoted by stabilizing Pdδ+ oxidic species at the interface of the Pd–metal oxide support with the help of EMSI effect, suggesting an intrinsic advantage of Pdδ+ in driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 66 publications
5
60
0
Order By: Relevance
“…He et al. studied the metal‐support interaction of drop‐cast Fe 2 O 3 on Pd and found that OER activity increased compared to the bare Pd electrode . Recently, Kauffman et al.…”
Section: Introductionmentioning
confidence: 99%
“…He et al. studied the metal‐support interaction of drop‐cast Fe 2 O 3 on Pd and found that OER activity increased compared to the bare Pd electrode . Recently, Kauffman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the efficient desorption of CO ads ‐like poisoning species at SnO x ‐Pt interface sites, SnO x /Pt(111) catalyst exhibited significant promotion of the catalytic performance toward EOR. Specially, He et al reported a series of similar metal‐oxide/Pd geometric nanostructures for oxygen evolution reaction (OER) in an alkaline solution. They demonstrated that the high valence Pd δ+ species located at the metal oxide‐Pd interfaces yield more additional d‐band vacancies, resulting in an improved adsorption of oxygenated species on surface and eventual enhanced OER activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the contrasting effects on band bending in WO 3 , the different oxidation states of Pd would result in different bonding and adsorption properties of oxygenated intermediates that drive water oxidation. 17,37 The charge extraction characteristics of the photoanodes were assessed by TPC measurements, whereby the charge extracted was measured as a function of time following excitation by a laser pulse (Figure 4). Pd(A)/WO 3 exhibits faster charge extraction rates than bare WO 3 , whilst charge extraction in Pd/WO 3 is slower.…”
Section: Resultsmentioning
confidence: 99%
“…An additional annealing step, post Pd deposition, is undertaken to investigate the recognised effects of co-catalyst oxidation state on performance. 17 We identify PdO as a promising OEC for acidic conditions that enhances the water oxidation activity and selectivity of WO 3 towards oxygen evolution, to yield an impressive FE of 92%. Further investigations into the photoanodes, including the charge carrier properties using transient techniques, reveal the role of PdO in inducing favourable band bending and tuning oxygen vacancy concentrations in WO 3 , to consequently improve electron transport through the nanoneedles.…”
Section: Introductionmentioning
confidence: 95%